Fatherhood in Times of Change - Staudt, Ana Cristina Pontello (2008)
Contemporaneity can be considered in its complexity, including the variety of interpersonal relations being a landmark of our times. We live in a doubtful moment concerning family and social roles, turning not so defined. This study aims to discuss how men are adapting to these demands of contemporary world, more specifically when it comes to being a father. Starting on a systemic perspective, paternity is considered to be constructed in the inter-relation of macro and micro systemic aspects of the social-historic-cultural context where it is situated. In this perspective, the definition of man and father in contemporary days is noticed to be getting more elastic and diffuse. Today, elements that reinforce the maintenance of a traditional structure in relations coexist, being the mother the main responsible for the family, with others representing the demand related to a bigger inclusion and participation of men in the private and family life.